Diptera survey in human corpses in the north of the state of Santa Catarina, Brazil - Anderson Gaedke; Denise Monique Dubet da Silva Mouga (Acta Biológica Catarinense, 2017)
Aiming to verify the species associated with the decomposition process carried out by necrophagous insects in human bodies, 11 species of dipterans were collected in 10 distinct cadavers from April 2014 to March 2016, resulting in individuals of the families Calliphoridae (Calliphora lopesi (Mello, 1962), Chrysomya megacephala (Fabricius, 1794), Chrysomya albiceps (Wiedemann, 1819), Hemilucilia segmentaria (Fabricius, 1805), Hemilucilia semidiaphana (Rondani, 1850), Lucilia cuprina (Wiedemann, 1830) and Lucilia eximia (Wiedemann, 1819)), Sarcophagidae (Peckia (Euboettcheria) australis (Fabricius, 1805) and Peckia (Sarcodexia) lambens (Wiedemann, 1830)), Muscidae (Muscidae sp.) and Stratiomyidae (Hermetia illucens (L. 1758)). Regarding the seasonality, dipterans were found in corpses in the four seasons, with distinct richness in each one. Dipterans were observed in corpses in all phases of decomposition (coloration, gaseous, colliquative and remains), the greater richness being verified in the gaseous phase. The data demonstrate differences in ecological succession, evidencing specialization of the insects found in relation to seasonality and the decomposition phase.